MENINGKATKAN PROSES BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN JASMANI DENGAN MATERI PASSING BAWAH BOLA VOLI MINI MELALUI PEMBELAJARAN KOOPERATIF MODEL STAD PADA SISWA KELAS V SD NEGERI 168/II SUMBER MULYA KABUPATEN BUNGO - Randi Eka Putra; Ade Marta Putra; Emisnawati Emisnawati (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2018)
The problem faced is learning Physical Education in class V is still implemented conventionally. Teachers still dominate learning by using the lecture method. While students only receive information from the teacher. In response to the above facts, it is necessary to conduct classroom action research (CAR). PTK aims to improve the learning process in a class, which in turn can improve the learning process of students in that class. In this case the STAD type cooperative learning model is one of the most effective and efficient learning models to be developed. This research is a classroom action research using aspects of planning, observation, action and reflection. This research was conducted in two cycles, where each cycle consisted of two meetings. The results of the study carried out in two cycles showed an increase in physical education learning using the STAD type cooperative learning model. seen from the learning outcomes obtained by students in each cycle, then in the first cycle the value of mastery learning obtained from 26 students was 57.69% while in the second cycle there was a very good increase, where the value of learning completeness obtained had reached 84 , 62% Thus, it can be said that the cooperative type STAD model can improve the learning of Physical Education in the fifth grade class of the Sumber Mulya District 168 / II Elementary School in Bungo.